2009
DOI: 10.1002/per.719
|View full text |Cite
|
Sign up to set email alerts
|

Mechanisms of the national character stereotype: How people in six neighbouring countries of Russia describe themselves and the typical Russian

Abstract: Altogether, 1448 individuals from six neighbouring countries of Russia in the Baltic Sea region (Finland, Estonia, Latvia, Lithuania, Poland and Belarus) described a 'typical' member of their own nation and a 'typical' Russian, as well as rated their own personality, using the National Character Survey (NCS). Results suggest that national character stereotypes are widely shared, temporally stable and moderately related to assessed personality traits, if all assessments are made using the same measurement instr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

9
98
1
3

Year Published

2009
2009
2020
2020

Publication Types

Select...
6
1
1

Relationship

2
6

Authors

Journals

citations
Cited by 109 publications
(112 citation statements)
references
References 34 publications
9
98
1
3
Order By: Relevance
“…Second, cross-national comparisons are needed to establish the cultural generalizability of the present findings. For instance, we may ask whether social orientation and adeptness would be particularly relevant to the Finnish context; in any case, these features run counter to the cultural representation of 'typical' Finns as introverted and closed to experience (Raelo et al, 2009). Moreover, different national economies have different ways of regulating the relationship between their higher education system and new skills strategies, and national variations shape how the students perceive the connection between higher educational qualifications and their future returns (Tomlinson, 2012).…”
Section: Discussionmentioning
confidence: 99%
“…Second, cross-national comparisons are needed to establish the cultural generalizability of the present findings. For instance, we may ask whether social orientation and adeptness would be particularly relevant to the Finnish context; in any case, these features run counter to the cultural representation of 'typical' Finns as introverted and closed to experience (Raelo et al, 2009). Moreover, different national economies have different ways of regulating the relationship between their higher education system and new skills strategies, and national variations shape how the students perceive the connection between higher educational qualifications and their future returns (Tomlinson, 2012).…”
Section: Discussionmentioning
confidence: 99%
“…The rst is an elicitation procedure for measuring personal values and personality traits. To achieve this we utilize two complementary methods: rst, a Personal Value Orientation (PVQ) survey tool (Schwartz et al, 2001) and a thirty-item Big5 survey tool (Realo et al, 2009), both used by social psychologists and economists (see Lönnqvist et al, 2009;Becker et al, 2012). The second key element is an exogenous subliminal manipulation of goal formations, i.e.…”
Section: Experimental Design and Proceduresmentioning
confidence: 99%
“…One week before the actual lab experiment, the subjects ll-out a 40 question PVQ questionnaire (Schwartz et al, 2001) and a thirty-item Big5 questionnaire (Realo et. al.…”
Section: Elicitation Of Personal Values and Personality Traitsmentioning
confidence: 99%
See 1 more Smart Citation
“…The inaccuracy of geographical personality stereotypes has been further confirmed in studies by McCrae, Terracciano, Realo, and Allik (2007) with Northern and Southern Italians and by Realo et al (2009) comparing Russian self-reported averages with perceptions by civilians of neighbor countries. Rogers and Wood (2010), however, did find that Americans' geographical personality stereotypes for openness to experience and neuroticism show considerable accuracy when compared with the results reported by Rentfrow et al (2008), with above-chance accuracy for agreeableness and extraversion.…”
Section: National Character Ratingsmentioning
confidence: 61%